The role of CPAP therapy in modulating the biological mechanisms of hypertension and aortic aneurysm in obstructive sleep apnea patients - Zhang, Yue; Sun, Wenfei; Wang, Wenqian; Yu, Feng; Ai, Yixia (Molecular & Cellular Biomechanics, 2025)
Background: Obstructive sleep apnea syndrome (OSAS) is closely related to multiple biological mechanisms, particularly its impact on the cardiovascular system. Long term OSAS may exacerbate issues such as hypertension, cardiovascular disease, and aortic disease. The aim of this study is to explore the effects of continuous positive airway pressure (CPAP) therapy on the biological mechanisms of OSAS patients, with a focus on analyzing the biological responses of blood pressure, respiration, and aortic changes. Method: This study retrospectively analyzed a case of a 75 year old male patient who was admitted with severe nighttime snoring and apnea symptoms, diagnosed with acute OSAS, aortic dissection, and hypertension. During the five-year follow-up after receiving CPAP treatment, the patient’s apnea index (AHI), blood pressure, changes in aortic diameter, and related biological indicators were monitored. Comprehensive evaluation of treatment efficacy using multiple biomarkers and electrocardiogram (ECG) data, combined with optimization analysis of respiratory rate and electrocardiogram signals using electrophysiological models. Result: After five years of treatment, the patient’s AHI significantly decreased to less than 6 beats per hour, blood pressure returned to normal, and the aortic diameter decreased from 4.5 cm to 4.1 cm. Electrophysiological analysis shows that CPAP treatment has a significant effect on adjusting respiratory patterns, restoring normal blood oxygen saturation, and optimizing the correlation between electrocardiogram and respiratory rate. In addition, using the TDNN model to estimate ECG signals shows a close biological correlation between respiratory rate and blood oxygen changes. Conclusion: CPAP treatment has a profound impact on the biological mechanisms of OSAS patients, effectively improving blood pressure control, reducing the progression of aortic disease, and optimizing changes in respiratory and electrocardiogram biomarkers. This study provides a new perspective for understanding the biological effects of OSAS treatment and provides a basis for optimizing future treatment strategies.